Convert the function into standard form:
y = (x + 4)(x - 6)
Show your work!!!
2 answers:
Hey!!
What is a standard form in a quadratic equation?
... y = ax² + bx + c
In this equation, x and y are points where as a,b and c are the constants.
We have:
... y = (x+4)(x-6)
... y = (x)(x)+(x)(-6)+(4)(x)+(4)(-6)
... y = x² - 6x + 4x - 24
Combining the like terms.
... y = x² - 2x - 24 <em>Is the standard form. </em>
Hope my answer helps!
You might be interested in
Answer:
X equals to -11
Step-by-step explanation:
Answer:
x=3
Step-by-step explanation:
subtract 5x from 7x
subtract 4 from 10
divide 2x and 6 by 2
Answer:
6x-7+32/4x+2
Step-by-step explanation:
Divide using polynomial division
The missing reason is you didn't put the actual question on here.
please show the full question.
Answer:
(-4,-3)
Step-by-step explanation:
The x value is -4 and the y value is -3